ANALISIS STRATEGI PEMASARAN SELADA HIJAU(Lactuca sativa L.) DI HIDROPONIK DZAKIYYAH FARM KABUPATEN SUKOHARJO - Pradana, Guntur Eka; Harinta, Yos Wahyu; Setyarini, Agung (Journal of Agribusiness, Social and Economic, 2022)
Hydroponic plant cultivation is increasingly being enjoyed by urban communities. This hydroponic trend emerged in line with the increasingly limited agricultural land in urban areas. The aim of this research is to determine internal and external factors, alternative strategies and determine strategic priorities in marketing. The basic method used is descriptive qualitative. The types of data used are primary and secondary data. Determining key persons or respondents using Purposive and Snowball sampling techniques. For data analysis methods use IFE, EFE, SWOT, and QSPM. Based on the results of the IFE matrix, 5 strengths and 5 weaknesses were identified with the results showing marketing distribution and not having a greenhouse as the main weakness, and the results of the EFE matrix identified 5 opportunities and 4 threats with the results showing regular customers as the biggest opportunity and competitors' pricing strategies and distribution strategies as the biggest threat. The SWOT matrix produces 8 alternative strategies, namely increasing the number of planting holes, creating a permanent partnership, embracing hydroponic beginners as partners, adjusting planting schedules to avoid natural risks, creating SOPs, creating social media, creating greenhouses, improving better management. The alternative is then decided through the QSPM matrix which places the W-O strategy, namely Making SOPs (Product Operational Standards) as a strategic priority with a Total Alternative Score of 7.721. The results of this research prioritize the strategy for creating SOPs, starting from standardizing products for production and partners, as well as maintaining existing quality so that it remains in demand by regular customers.